(untitled) (Journal of Business Management and Accounting, 2012)
Malaysia is on the track to achieve full convergence and adoption of the International Financial Reporting Standards (IFRSs) by 2012. This study seeks to find out the extent of compliance with IFRS 101 ‘P resentation of Financial Statements’ before the effective date. Using total disclosure index (TDI), the findings shows that most of Malaysian Ace Market companies have complied with IFRS 101. The present study also indicates that the Cumulative Market Adju sted Return (CMAR) is positive and significant for both partial and full compliance of IFRS 101 among the Malaysian Ace Market companies. Multivariate regression analysis further provides a lack of significant association between CMAR and announcement of e arnings (i.e. EPS). Nevertheless, the percentage of independent directors on the board (BDIND) is found to be a positive and a significant corporate governance variable that associates with CMAR. These findings imply that policy makers and regulators shoul d encourage Ace Market companies to have the most optimal number of independent board of directors for future improvements of CMAR